2012
DOI: 10.1016/j.jand.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Eating Habit Modification Predicts Weight Change in Overweight, Postmenopausal Women: Results from the WOMAN Study

Abstract: Background Standard behavioral obesity treatment produces poor long-term results. Focusing on healthy eating behaviors, rather than caloric intake, may be an alternative strategy. Furthermore, important behaviors might differ for short- vs. long-term weight control. Objective To describe and compare associations between changes in eating behaviors and weight after 6 and 48 months Design Secondary analysis of data collected during a randomized weight loss intervention trial with 48-month follow-up Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…Studies have shown that weight is gradually regained 6 months after weight loss efforts, owing to decreases in time and effort spent on weight control, perceived inadequate long-term rewards for weight control behaviors, as well as differences in eating habit behaviors in short- and long-term time periods (31–33). In addition, other efforts have been made to assess differences that lead to weight loss versus long-term weight maintenance (34).…”
Section: 1 Introductionmentioning
confidence: 99%
“…Studies have shown that weight is gradually regained 6 months after weight loss efforts, owing to decreases in time and effort spent on weight control, perceived inadequate long-term rewards for weight control behaviors, as well as differences in eating habit behaviors in short- and long-term time periods (31–33). In addition, other efforts have been made to assess differences that lead to weight loss versus long-term weight maintenance (34).…”
Section: 1 Introductionmentioning
confidence: 99%
“…Overall, weight loss was 2.6% greater in the intensively treated group, and loss to follow‐up was 6%. The second study is a 4‐year study in 481 postmenopausal women with overweight and obesity; 42% of the participants were successful in losing 3‐11% of their initial weight, and the percentage successful in losing at least 12% was 15% . Weight gain of at least 3% was observed in 19% of the participants; loss to follow‐up was 18%.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth study reports 50 out of 122 participants (41%) being successful at losing at least 2 kg (2.6%) of their body weight after a 3‐year‐long long diet intervention . Three out of these four studies also report mean weight loss and are thus also included in the next paragraph and Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Each item was scored on a scale of 1 to 5, with 5 being associated with low food intake. 19,20 Cholesterol-Lowering Diet Self-efficacy ScaleYShort Form Cholesterol-Lowering Diet Self-efficacy Scale-Short Form (CLDSES-SF), 40-item scale, was developed to measure the level of efficacy expectancy for following a cholesterol-lowering diet among patients with hypercholesterolemia. The Restaurant and Recipes subscale score indicated the number of low-fat choices made in restaurants (a score of 5 was given for each low-fat choice made when eating in restaurants).…”
Section: Connor Diet Habit Surveymentioning
confidence: 99%